KUFRI FRYSONA: FIRST HIGH YIELDING POTATO VARIETY FOR FRENCH FRIES IN INDIA - Singh, S V; Pandey, S K; Kumar, Dinesh; Marwaha, R S; Manivel, P; Kumar, Parveen; Singh, B P; Bhardwaj, Vinay (Potato Journal, 2013)
Frozen French fries are the most popular processed potato product throughout the world. India lacks a suitable potato variety for French fry production. The variety Kufri Frysona has been developed to fill this gap to provide suitable raw material to French fry industry. Kufri Frysona gives tuber yields higher than the presently used Indian processing varieties Kufri Chipsona-1 and Kufri Surya. It also excels them in giving high proportion of oblong to long French fry grade tubers and better French fries in taste, texture and colour. Kufri Frysona possesses high field resistance to late blight disease and keeps well under country storage conditions for over 8 weeks.